Covid-19 pandemic effect on MSMEs in Rawa Bambu Slums, Kalibaru Village, Bekasi City - Augustin, Avina Nilam; Sunarti, Sunarti (Regional Development Information Center, Universitas Sebelas Maret, 2023)
RW 08 Rawa Bambu Settlement has been upgraded and is in better condition, so there is a new activity plan titled 'water recreation,' which will develop MSMEs in RW 08 in order to improve the local community's economy. However, the new activity plan has been pushed back due to the Covid-19 pandemic. This study aimed to examine the effect of Covid-19 pandemic on MSMEs in RW 08 Rawa Bambu slums, Kalibaru Village, Bekasi City. Data were collected quantitatively by questionnaires to 30 entrepreneurs, and then analyzed using simple linear regression. The findings revealed that the Covid-19 pandemic has a significant effect on MSMEs in RW 08 Rawa Bambu based on changes in their socioeconomic activities. Socioeconomic activities that were impacted included a decrease in the community's ability to save (24,5%), a decrease in the income rate (23,1%), product sales area changes (17,6%), and management efforts for RW 08 Rawa Bambu. The rate of community economic improvement has decreased (17.6%) and the rate of product demand has decreased (17.2%). The decrease in socioeconomic activities at RW 08 Bambu demonstrates the community's inability to meet its needs or survive as a result of the Covid-19 pandemic.